ANALYSIS OF THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT, EDUCATION, OPEN UNEMPLOYMENT, MINIMUM WAGES AND HUMAN DEVELOPMENT INDEX ON POVERTY OF WEST NUSA TENGGARA PROVINCE IN 2012-2017 (CASE STUDY OF 10 DISTRICTS/CITIES) - Bunga Mersiana (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aimed to analyze the effect of independent variables, Gross Regional Domestic Product (GRDP), Education, Open Unemployment, Minimum Wages and Human Development Index (HDI) on the dependent variable, Poverty Rate of West Nusa Tenggara (NTB) province in 2012-2017. The data used in this research was panel data which is the combination of time series and cross-section data of poverty in 10 districts or cities in NTB province during the period 2012- 2017, produce 60 observations. This research used secondary data analysis which sourced from Central Bureau of Statistics, National Labor Force Survey, Ministry of Labor and Transmigration of NTB Province, National Development Planning Board, National Socio Economic Survey and Scientific Researches. This research used Eviews 9 as data regression processing method. Results from this research showed that the effect of Gross Regional Domestic Product (GRDP), Education, Open Unemployment, Minimum Wages and Human Development Index (HDI) on Poverty Rate. This was shown by the results of the regression analysis of Adjusted R squared by 0,7302. It means 73,02 % the variation of independent variables (Gross Regional Domestic Product, Education, Open Unemployment, Minimum Wages and Human Development Index) can explain the dependent variable (Poverty Rate in West Nusa Tenggara Province) and the remaining 26,98 % is explained by other factors outside the model. Based on regression panel test result, Gross Regional Domestic Product (GRDP) towards Poverty has negative and insignificant influence partially. The increasing of Gross Regional Domestic Product in city or district in NTB province as much as 1%, will decrease Poverty as much as 0.08%. Education towards Poverty has negative and insignificant influence partially. The increasing of Education in city or district in NTB Province as much as 1%, will decline poverty as much as much as 1,12%. Open Unemployment towards Poverty has negative and insignificant influence partially. The increasing Unemployment in city or district in NTB province as much as 1%, will decrease poverty as much as 0,0388%. Minimum Wages towards Poverty has positive and insignificant influence partially. The increasing Minimum Wages in city or district in NTB province as much as 1% will increase poverty as much as 0,30%. Human Development Index towards Poverty has negative and significant influence partially. The Increasing Human Development Index in city or district in NTB province as much as 1% will decrease poverty as much as 2,95%. Meanwhile, Gross Regional Domestic Product (GRDP), Education, Open Unemployment, Minimum Wages and Human Development Index (HDI) simultaneously have significant influence to poverty. The variation of poverty variable can be explained by the five independent variables as much as 73.02%, or in other words the contribution of Gross Regional Domestic Product, Education, Open Unemployment, Minimum Wages and Human Development Index to influence Poverty in NTB province as much as 73.02% while the remaining 26,98% is the contribution of the other variables that are not addressed in this research. In this research was found that Education, Open Unemployment, Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) negatively affect Poverty rate while Minimum Wages positively affect Poverty rate.Key Words: Gross Regional Domestic Product, Education, Open Unemployment, Minimum Wages, Human Development Index and Poverty Rate. A